The Strong State And Pancasila: Reflecting Human Rights in the Indonesian Democracy - Zezen Zaenal Mutaqin (Constitutional Review, 2016)
The rights of every Indonesian citizens are protected by the 1945 Constitution. Does the reality matches with the normative regulations? Does democratization improves the protection of human rights especially in term of the religious freedom? We find that there is a discrepancy between the ideal written constitution and the reality. In this following essay I argue that the failure of Indonesian democratic regimes to protect human rights is the result of the lack of "stateness". The ideal of "stateness" is referring to Fukuyama idea that is "the ability of state to plan and execute policies and to enforce law". I will present the argument that the weakness of the administration cause by an ambiguity in the interpretation of the Indonesia ideology, Pancasila (the Five-Principles). This paper will firstly discuss the idea of strong state and its relation to the protection of human rights. Alongside the theoretical examination of the concept, I will discuss the weakness of democratic regimes in Indonesia to protect human rights. This will be followed by an examination of the core argument of the paper, argue that the principle cause of the state weakness lies on the ambiguity of the administration to interpret Pancasila.